A Student Response to the Arduino Uno-Based Uniformly Accelerated Motion Experiment Equipment in Basic Physics I Course - Jufrida Jufrida; Rahma Dani; Yanvito Purba (Jurnal Penelitian Pendidikan IPA, 2025)
This research is based on technological advancements. As time progresses, numerous components have evolved in terms of functional efficiency, benefits, and physical aspects. In this context, a study was conducted to examine students' responses to the experimental equipment. The research was carried out in the physics laboratory of the Faculty of Teacher Training and Education at Jambi University. The aim of this study was to determine students' responses to technology-based experimental equipment. The subjects of this study were regular 2022 physics education students. The instrument used was a student response questionnaire. The data collection technique in this study was quantitative and analyzed using descriptive statistics with a Likert scale. The results of this study showed an average interest level of 80.1% towards the experimental equipment, categorized as very good. The conclusion of this study is that the Arduino Uno-based experimental equipment received positive responses from the respondents